2022
DOI: 10.1128/spectrum.01312-22
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anti-Inflammatory Activities of MAF-1-Derived Antimicrobial Peptide Mt6 and Its D-Enantiomer D-Mt6 against Acinetobacter baumannii by Targeting Cell Membranes and Lipopolysaccharide Interaction

Abstract: Around 700,000 people worldwide die each year from antibiotic-resistant pathogens. Acinetobacter baumannii in clinical specimens increases year by year, and it is developing a strong resistance to clinical drugs, which is resulting in A. baumannii becoming the main opportunistic pathogen. Antimicrobial peptides show great potential as new antibacterial drugs that can replace traditional antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Previous investigations have shown that the neutralization of AMPs with LPS might be one of the anti-inflammatory actions of AMPs 21 , 22 . D-Mt6, designed from the hemlymphocytes of housefly larvae, showed great immunoregulatory activity against LPS-induced inflammation through its LPS neutralization and suppression of MAPK signaling 23 . In addition to the neutralization of LPS, AMPs could intervene in Toll-like receptor (TLR) signaling pathways with potent antiendotoxin properties 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that the neutralization of AMPs with LPS might be one of the anti-inflammatory actions of AMPs 21 , 22 . D-Mt6, designed from the hemlymphocytes of housefly larvae, showed great immunoregulatory activity against LPS-induced inflammation through its LPS neutralization and suppression of MAPK signaling 23 . In addition to the neutralization of LPS, AMPs could intervene in Toll-like receptor (TLR) signaling pathways with potent antiendotoxin properties 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study produced three analogues of the AMP CXCL14-C17 and the analogues were able to act on antibiotic-resistant bacteria and could have promising anti-inflammatory properties due to the inhibition of the tumor necrosis factor (TNF) and interleukin (IL-1β) [80]. Similarly, a study has been shown to produce two analogues (Mt6 and D-Mt6) of the AMP MAF-1 [81]. The analogues were observed to be stable and active against A. baumannii under many physiological settings as well as decreased TNF and IL-1β expression which suggests improved anti-inflammatory properties.…”
Section: Amps With Anti-inflammatory Propertiesmentioning
confidence: 99%
“…These AMPs drastically decrease expression of IL-β and TNF-α in LPS-stimulated macrophages. This capability is likely due to dual abilities to directly bind LPS and to inhibit the LPS-activated MAPK signaling pathways in macrophages [ 48 ]. Although this study demonstrated the mechanism by which D-Mt6 reduces inflammatory cytokine expression levels, it has not yet been confirmed how this AMP induces cell lysis and death.…”
Section: Regulatory Effect Of Amps On Macrophagesmentioning
confidence: 99%